Protein Kinase C Regulation of 12-Lipoxygenase-Mediated Human Platelet Activation - Yeung, Jennifer (The American Society for Pharmacology and Experimental Therapeutics, 2012)
Platelet activation is important in the regulation of hemostasis and thrombosis. Uncontrolled activation of platelets may lead to arterial thrombosis, which is a major cause of myocardial infarction and stroke. After activation, metabolism of arachidonic acid (AA) by 12-lipoxygenase (12-LOX) may play a significant role in regulating the degree and stability of platelet activation because inhibition of 12-LOX significantly attenuates platelet aggregation in response to various agonists. Protein kinase C (PKC) activation is also known to be an important regulator of platelet activity. Using a newly developed selective inhibitor for 12-LOX and a pan-PKC inhibitor, we investigated the role of PKC in 12-LOX-mediated regulation of agonist signaling in the platelet. To determine the role of PKC within the 12-LOX pathway, a number of biochemical endpoints were measured, including platelet aggregation, calcium mobilization, and integrin activation. Inhibition of 12-LOX or PKC resulted in inhibition of dense granule secretion and attenuation of both aggregation and αIIbβ(3) activation. However, activation of PKC downstream of 12-LOX inhibition rescued agonist-induced aggregation and integrin activation. Furthermore, inhibition of 12-LOX had no effect on PKC-mediated aggregation, indicating that 12-LOX is upstream of PKC. These studies support an essential role for PKC downstream of 12-LOX activation in human platelets and suggest 12-LOX as a possible target for antiplatelet therapy.